PERSONALIZED MANAGEMENT OF MALE SEXUAL DYSFUNCTION: INTEGRATING PELVIC FLOOR REHABILITATION AND MODERN ANDROLOGY (Vietnam Journal of Community Medicine, 2026)
Male sexual dysfunction represents a complex group of disorders involving the interaction of vascular, hormonal, neuropsychological, and functional mechanisms, rather than a disease confined to a single organ system. Traditional treatment models, which have primarily focused on pharmacotherapy and symptom-based management, often show limited effectiveness in patients with complex, persistent, or treatment-resistant conditions. Among the contributing mechanisms, pelvic floor dysfunction has increasingly been recognized as an important yet underappreciated factor associated with erectile dysfunction, premature ejaculation, chronic pelvic pain syndrome, and post-pelvic surgery dysfunction. Recent evidence suggests that pelvic floor rehabilitation—including pelvic floor muscle training, relaxation therapy, biofeedback, and selected neuromuscular stimulation technologies—may improve erectile function, ejaculatory control, pain symptoms, and urinary continence, particularly when integrated into a multimodal andrology strategy. This review provides an updated overview of the role of the pelvic floor in male sexual dysfunction, summarizes current clinical evidence regarding the efficacy of pelvic floor rehabilitation, and proposes a personalized, phenotype-driven management model in which pelvic floor rehabilitation becomes an integral component of modern andrology.
Keywords: male sexual dysfunction; pelvic floor dysfunction; pelvic floor rehabilitation; personalised andrology